Existence of Conformal Metrics with Prescribed Q-Curvature - Mohammed Ali Al-Ghamdi; Hichem Chtioui; Afef Rigane (Abstract and Applied Analysis)
We consider the problem of existence of conformal metrics with prescribed Q-curvature on standard sphere . Under the assumption that the order of flatness at critical points of prescribed Q-curvature function is , we give precise estimates on the losses of the compactness, and we prove new existence and multiplicity results through an Euler-Hopf type formula.